Oceanographic basis of the global surface distribution of Prochlorococcus ecotypes. - Bouman, H; Ulloa, O; Scanlan, D; Zwirglmaier, K; Li, W; Platt, T; Stuart, V; Barlow, R; Leth, O; Clementson, L; Lutz, V; Fukasawa, M; et al. (2006)
By using data collected during a continuous circumnavigation of the Southern Hemisphere, we observed clear patterns in the population-genetic structure of Prochlorococcus, the most abundant photosynthetic organism on Earth, between and within the three Southern Subtropical Gyres. The same mechanisms that were previously invoked to account for the vertical distribution of ecotypes at local scales accounted for the global (horizontal) patterns we observed. Basin-scale and seasonal variations in the structure and strength of vertical stratification provide a basis for understanding large-scale horizontal distribution in genetic and physiological traits of Prochlorococcus, and perhaps of marine microbial communities in general.